Daniel Morris. 2013. Lyric Encounters: Essays on American Poetry from Lazarus and Frost to Ortiz Cofer and Alexie. - Jimenez-Munoz, Antonio J. (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2016)
.